The Use of Acoustic Emission Method for Diagnosis of Damage of Pneumatic Cylinders - Mazal, Pavel; Vlašic, František; Mahmoud, Houssam (German Society for NDT, 2016)
The paper presents the latest results obtained in the course of the project Technology Agency of the Czech Republic, which aims to create a new diagnostic system for checking the function of pneumatic cylinders using acoustic emission. There are compared the records of the AE signal from the undamaged pneumatic cylinders and similar entries from cylinders containing artificial defects. Records of signals are monitored by modern analysers DAKEL IPL with full sampling of the signal. Based on the analysis of large data sets are selected suitable AE signal parameters, which can be used for more accurately diagnostics of condition of tested devices which could be used for constructing of analyser for testing of pneumatic devices.

The paper presents the latest results obtained in the course of the project Technology Agency of the Czech Republic, which aims to create a new diagnostic system for checking the function of pneumatic cylinders using acoustic emission. There are compared the records of the AE signal from the undamaged pneumatic cylinders and similar entries from cylinders containing artificial defects. Records of signals are monitored by modern analysers DAKEL IPL with full sampling of the signal. Based on the analysis of large data sets are selected suitable AE signal parameters, which can be used for more accurately diagnostics of condition of tested devices which could be used for constructing of analyser for testing of pneumatic devices.
The Use of Acoustic Emission Method for Diagnosis of Damage of Pneumatic Cylinders
Keywords: acoustic emission; signal; pneumatic valve; damage; acoustic emission; signal; pneumatic valve; damage